2003
DOI: 10.4049/jimmunol.171.10.5034
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of IL-10 Activity and Signaling by IFN-γ

Abstract: One important mechanism of cross-regulation by opposing cytokines is inhibition of signal transduction, including inhibition of Janus kinase-STAT signaling by suppressors of cytokine signaling. We investigated whether IFN-γ, a major activator of macrophages, inhibited the activity of IL-10, an important deactivator. Preactivation of macrophages with IFN-γ inhibited two key anti-inflammatory functions of IL-10, the suppression of cytokine production and of MHC class II expression. Gene expression profiling show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
124
0
5

Year Published

2005
2005
2015
2015

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 130 publications
(137 citation statements)
references
References 45 publications
7
124
0
5
Order By: Relevance
“…It has been long appreciated that Stat1 and Stat3 have opposing biological functions, and evidence is emerging that these two transcription factors antagonize each other's action in cytokine signal transduction pathways (9,28,38,39). Our results further support the notion that Stat1 suppresses the activation of gene expression mediated by Stat3-dependent pathways (schematically illustrated in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…It has been long appreciated that Stat1 and Stat3 have opposing biological functions, and evidence is emerging that these two transcription factors antagonize each other's action in cytokine signal transduction pathways (9,28,38,39). Our results further support the notion that Stat1 suppresses the activation of gene expression mediated by Stat3-dependent pathways (schematically illustrated in Fig.…”
Section: Discussionsupporting
confidence: 80%
“…Analysis of these data, kindly provided by Drs. This mechanism, which operates within hours, may be different from what occurs when cells are primed for 1 or 2 days before adding a stimulus (Hu et al, 2006) (Herrero et al, 2003). When using a system with a 2day priming period then this will alter the entire gene expression program of a cell with many indirect effects (Herrero et al, 2003).…”
Section: Effect Of Ifn On Binding Of Stat1 and Stat3 In The Intact Numentioning
confidence: 99%
“…For example, proinflammatory IFN-␥ activates predominantly STAT1 (31) while the potent anti-inflammatory IL-10 activates predominantly STAT3 (22,32). More pleiotropic cytokines, such as IL-6 and IFN-␣, activate both STAT1 and STAT3 (33,34) and we have shown that conditions that augment STAT1 activation, such as priming macrophages (Ms) 3 with IFN-␥, increase the proinflammatory properties of cytokines and can even confer activating functions to 26,35). IL-27 activates both STAT1 and STAT3 in myeloid cells and thus has the potential to induce both proinflammatory and anti-inflammatory effects.…”
mentioning
confidence: 99%